Returning of Medical Record Documents Among Hospitalized Patients: Literature Review - Ida Nurmawati; Sari Handayani (Universitas Aisyah Pringsewu, 2021)
The delays in returning inpatient medical record documents in the hospital are still common. The purpose of this study was to analyze the delays in returning inpatient medical record document factors in the hospital. The study used the literature review method to 16 articles which were searched through Google Scholar, GARUDA, Rama Repository, and E-Library Politeknik Negeri Jember. The result of the research showed from 16 analyzed articles, the delays in returning inpatient medical record documents caused by the lack of doctor’s discipline in filing medical record documents completely, there is no reward and punishment for obedient officers, lack of the standard operating procedure socialization in returning inpatient medical record documentation for the nurses and doctors, the distance between inpatient and medical record unit is too far, there are no facilities for helping in returning of medical record document activity in medical record unit such as trolley. The suggestion that could be given is, they need to conduct socialization of the standard operational procedure in returning inpatient medical record documents at the hospital regularly. So that, the nurses and doctors are always paying attention to the specified time in returning inpatient medical record documents.Abstrak: Keterlambatan pengembalian DRM pasien rawat inap di rumah sakit masih sering terjadi. Tujuan dari penelitian ini adalah untuk menganalisis faktor penyebab keterlambatan pengembalian DRM pasien rawat inap di rumah sakit. Penelitian dilakukan dengan menggunakan metode studi literatur terhadap 16 artikel penelitian yang ditelusuri melalui Google Scholar, GARUDA, Rama Repository, dan E-Library Politeknik Negeri Jember. Hasil penelitian menunjukkan bahwa dari 16 artikel yang dianalisis, keterlambatan pengembalian DRM pasien rawat inap di rumah sakit disebabkan oleh kurangnya kedisiplinan DPJP dalam melakukan pengisian DRM secara lengkap, tidak terdapatnya reward dan punishment terhadap petugas, kurangnya sosialisasi SOP pengembalian DRM pasien rawat inap kepada perawat dan DPJP, jarak antara unit rawat inap dengan unit rekam medis yang terlalu jauh, dan belum terdapatnya sarana untuk menunjang kegiatan pengembalian DRM ke unit rekam medis seperti troli. Saran yang dapat diberikan adalah perlu diadakan kegiatan sosialisasi SOP pengembalian DRM pasien rawat inap di rumah sakit secara berkala agar perawat dan DPJP selalu memperhatikan standar waktu pengembalian DRM yang telah ditentukan.